The Trends Research of Conceptual Mastery in Students' Physics Learning (2015-2024): A Systematic Review - Aris Doyan; Susilawati Susilawati; Syarful Annam; Lalu Muliyadi; Ruth Rize Paas Megahati; Risnawati Agustin Hutabarat; Muhammad Ikhsan; Nuraini Rachma Ardianti (Postgraduate, University of Mataram, 2024)
To support the improvement of 21st century skills, students must have good concept mastery first. This is in accordance with one of the goals of education is to master the concepts studied. Mastery of concepts is important for students to have because it can determine the level of success of students in participating in learning activities and whether the teacher is successful or not in fostering enthusiasm, encouragement, interest and student learning outcomes with classroom management. This research aims to identify and analyze research trends in the conceptual mastery in physics learning. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research on conceptual mastery in physics learning that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that the trend of research on the conceptual mastery in physics learning indexed by Google Scholar from 2015 to 2024 experienced a fluctuating increase. However, in 2023 there will be a decline in the research trend on conceptual mastery in physics learning. There are many documents in the form of articles, proceedings, book, chapters, edited books and monograph that discuss research into the conceptual mastery in physics learning. Keywords that are often used in research of conceptual mastery are conflict cognitive approach, discovery model, STEM, effectiveness, etc.